Daily Math : From Concepts To Habits - Wanda Nugroho Yanuarto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
Math expresses itself everywhere, in almost every face of life, in nature all around, and in the technologies in hands. Mathematics is the language for the universe. The purpose of this study are introducing math in concept and deliver it into application life for students. The situational problem as the starting point helps students to relate what they learn to problems in daily life , and construct that are related to real situations. It is take place in math education subject in Teacher Training and Education Faculty at The University of Muhammadiyah Purwokerto, Indonesia. Authors start with projects that have applications of math and continue with the closely related topic of concept math. Then go on to the timely topic of concepts of math (exponents, multiplying & dividing integers, multiplying decimals, and percent), the application of which are immediately felt when the students face in cooking by numbers, home decorating, populating growth, saving & credit, and playing to win. It presents four projects in home, restaurant, school or college, and bank. In the section on society it touchs upon topics like cooking recipe, decorating a house, populating, account saving, and probability issues